Ø§Ù„ØªÙØ³ÙŠØ± Ø§Ù„Ø¹Ù‚Ù„Ø§Ù†ÙŠ Ù„Ù„Ù‚Ø±Ø¢Ù†: Ù…ÙˆÙ‚Ù Ø£ØÙ…Ø¯ Ø®Ø§Ù† Ù…Ù† Ø§Ù„ØªÙØ³ÙŠØ± Ø¨Ø§Ù„Ø±Ø£ÙŠ - Maghribi, Hamdan (DINIKA : Academic Journal of Islamic Studies, 2017)
Qurâ€™anic interpretation with a rational style usually led to controversy. It gives a large portion for the mind to explore the scripture interpretation realm. Nevertheless, a rational style of interpretation is required to open the horizon of Qurâ€™anic exegesis, especially with regard to kauniyah verses. Sir Syed Ahmad Khan, one of the reformist thinkers of India, gave a large portion of the Qur'anic interpretation. He gave a wide ratio of freedom in interpreting and understanding the Qur'an. Based on his works, this paper finds that Khan has not paid much attention to the Islamic scholastic theology in his style of Qurâ€™anic exegesis. He only mentioned it briefly; the properties of God, the Throne ('Arsy), seeing God in the afterlife. He prefers to reform the concept of Classical Ê¿Ilm al-KalÄm and the renewal of Ê¿Ilm al-KalÄm. He is very well-known to have a strong preference towards Greek philosophy. The kauniyah verses must be interpreted and viewed from the framework of modern science, because it is a necessity and the answer to the challenge that Islam and the Qur'an are the teachings which are Shalihun likulli zaman wa makan, for it must always be in line with the development of science.Keywords: Sir Syed Ahmad Khan; Tafsir bi al ra'yi; Ê¿Ilm al-KalÄm